Respon Pertumbuhan dan Produksi TanamanJagung Manis (Zea Mays Saccharata Sturt.)Terhadap Pemberian Kompos Kulit Buah Kopi dan NPK - Petrus Lukmana Hamonangan Silalahi; Syafrina Syafrina; Husna Yetti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The aim of this research is to know the effect of composting of coffee peel and NPK fertilizer on the growth and production of sweet corn and to know the best dose of the treatment. This research conducted in experimental garden of Faculty of Agriculture Riau University for four months starting from June to September 2017. This research was conducted using a randomized block design (RBD) consisting of two factors. The first factor of fruit coffee compost was the second factor of NPK fertilizer. The data obtained in the field were analyzed statistically. The results of the real variance analyzed using a real 5% True Difference Test (TDT). The observed parameters were plant height, diameter of stem, time of male flower, time of female flower, weight of cob weighted per plant, weight of cob weighted per plot, cob weight without corn husk per plant, cob diameter without weight and number of rows of seeds. The results showed that the increased dose of coffee fruit compost did not affect the growth and production of sweet corn while the increase of NPK fertilizer dosage generally increased the growth and production of sweet corn plant. The interaction of fruit coffee compost and NPK fertilizer has no effect in improving the growth and production of sweet corn plants. Keywords: Sweet corn, coffee fruit compost and NPK